Informed options trading prior to bankruptcy filings - Ge, LI (Institutional Knowledge at Singapore Management University, 2019)
Prior evidence on pre-bankruptcy-filing informed trade is mixed. The inconclusive findings might result from the sole focus on stock trading. We reassess the presence of pre-filing informed and insider trades by examining the information content of options trading before bankruptcy announcements. We find that bankruptcy filing returns are not significantly related to pre-filing insider stock trading. However, filing returns are significantly negatively related to pre-filing insider and informed options trading. The informational content of options trading reduces with options illiquidity and the amount of information impounded into pre-filing stock prices.